Phase protection of Fano-Feshbach resonances - Blech, Alexander; Shagam, Yuval; Holsch, Nicolas; Paliwal, Prerna; Skomorowski, Wojciech; Rosenberg, John W.; Bibelnik, Natan; Heber, Oded; Reich, Daniel M.; Narevicius, Edvardas; Koch, Christiane P. (Nature Communications, 2020)
Decay of bound states due to coupling with free particle states is a general phenomenon occurring at energy scales from MeV in nuclear physics to peV in ultracold atomic gases. Such a coupling gives rise to Fano-Feshbach resonances (FFR) that have become key to understanding and controlling interactions—in ultracold atomic gases, but also between quasiparticles, such as microcavity polaritons. Their energy positions were shown to follow quantum chaotic statistics. In contrast, their lifetimes have so far escaped a similarly comprehensive understanding. Here, we show that bound states, despite being resonantly coupled to a scattering state, become protected from decay whenever the relative phase is a multiple of π. We observe this phenomenon by measuring lifetimes spanning four orders of magnitude for FFR of spin–orbit excited molecular ions with merged beam and electrostatic trap experiments. Our results provide a blueprint for identifying naturally long-lived states in a decaying quantum system.
CRIS-Team Scopus Importer:2023-04-20